2021
DOI: 10.4149/neo_2021_201208n1328
|View full text |Cite
|
Sign up to set email alerts
|

microRNA-204 shuttled by mesenchymal stem cell-derived exosomes inhibits the migration and invasion of non-small-cell lung cancer cells via the KLF7/AKT/HIF-1α axis

Abstract: Non-small-cell lung cancer (NSCLC) remains the leading cause of cancer-related death worldwide.Accumulating researches have highlighted the ability of exosome-encapsulated microRNAs (miRNAs or miRs) as potential circulating biomarkers for lung cancer. The current study aimed to evaluate the significance of mesenchymal stem cells (MSCs)-derived exosomal miR-204 in the invasion, migration, and epithelial-mesenchymal transition (EMT) of NSCLC cells. Initially, the expression of miR-204 in human NSCLC tissues and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 29 publications
(34 reference statements)
1
14
0
Order By: Relevance
“…MiR-204 [ 33 ], miR-193a [ 5 ] and miR-144 [ 10 ] are included in these miRNAs. The data from this study further complement and support the role of Exo in delivering miRNA [ 34 ].…”
Section: Discussionsupporting
confidence: 77%
“…MiR-204 [ 33 ], miR-193a [ 5 ] and miR-144 [ 10 ] are included in these miRNAs. The data from this study further complement and support the role of Exo in delivering miRNA [ 34 ].…”
Section: Discussionsupporting
confidence: 77%
“…Several studies have confirmed the importance of the biological functions of MSCs in the progression of NSCLC (Fregni et al, 2018;Gu et al, 2020;Liang et al, 2020;Liu et al, 2021;Yin et al, 2021). MSCs are known to cause transcriptional changes in lung cancer cells, leading to increased expression of MMP9.…”
Section: Discussionmentioning
confidence: 90%
“…In the TME, MSCs participate in material transportation and intercellular information transmission by secreting exosomes, and regulate tumor cell viability ( Liu et al, 2021 ; Mohr et al, 2021 ; Wang W. et al, 2021 ; Muralikumar et al, 2021 ; Yin et al, 2021 ). Co-culturing MSCs with pancreatic cancer cells shows enhanced expression of metastatic cytokines CCL2 and IL6, which are produced by the stem cells.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations